RNA sequencing-based transcriptome profiling of cardiac tissue implicates novel putative disease mechanisms in FLNC-associated arrhythmogenic cardiomyopathy. (1st March 2020) - Hall, Charlotte L.; Gurha, Priyatansh; Sabater-Molina, Maria; Asimaki, Angeliki; Futema, Marta; Lovering, Ruth C.; Suárez, Mari Paz; Aguilera, Beatriz; Molina, Pilar; Zorio, Esther; Coarfa, Cristian; Robertson, Matthew J.; et al.
Abstract: Arrhythmogenic cardiomyopathy (ACM) encompasses a group of inherited cardiomyopathies including arrhythmogenic right ventricular cardiomyopathy (ARVC) whose molecular disease mechanism is associated with dysregulation of the canonical WNT signalling pathway. Recent evidence indicates that ARVC and ACM caused by pathogenic variants in the FLNC gene encoding filamin C, a major cardiac structural protein, may have different molecular mechanisms of pathogenesis. We sought to identify dysregulated biological pathways in FLNC -associated ACM. RNA was extracted from seven paraffin-embedded left ventricular tissue samples from deceased ACM patients carrying FLNC variants and sequenced. Transcript levels of 623 genes were upregulated and 486 genes were reduced in ACM in comparison to control samples. The cell adhesion pathway and ILK signalling were among the prominent dysregulated pathways in ACM. Consistent with these findings, transcript levels of cell adhesion genes JAM2, NEO1, VCAM1 and PTPRC were upregulated in ACM samples. Moreover, several actin-associated genes, including FLNC, VCL, PARVB and MYL7, were suppressed, suggesting dysregulation of the actin cytoskeleton. Analysis of the transcriptome for dysregulated biological pathways predicted activation of inflammation and apoptosis and suppression of oxidative phosphorylation and MTORC1 signalling in ACM. Our data suggests dysregulated cell adhesion and ILK signalling as novel putative pathogenic mechanisms of ACM caused by FLNC variants which are distinct from the postulated disease mechanism of classic ARVC caused by desmosomal gene mutations. This knowledge could help in the design of future gene therapy strategies which would target specific components of these pathways and potentially lead to novel treatments for ACM. Graphical abstract: Design, methodology and main findings: analysis of transcriptome profiles of cardiac tissue from deceased ACM patients with FLNC variants. Unlabelled Image Highlights: Transcriptome profiling of fixed LV samples from ACM cases with FLNC variants Dysregulated pathways include the ILK signalling and the cell adhesion pathways. Possible dysregulation of the actin cytoskeleton in FLNC -associated ACM Transcript levels of cell adhesion pathway genes were upregulated in ACM hearts. Dysregulated cell adhesion is a putative mechanism in ACM caused by FLNC variants.